Hydrodynamic modeling for better understanding of flood and Manmade interventions in the Sungai Sarawak - Putuhena, F.J.; Said, S.; Mah, D.Y.S.; Ahmad Bustami, R. (Universiti Malaysia Sarawak, UNIMAS, 2007)
This paper reviews the river modelling case studies of the tributaries of Sungai Sarawak system, namely Sungai Maong, Sungai Sarawak Kanan and Sungai Sarawak kiri to reflect the risk of flooding changes imposed by the major hydraulic structures like the Kuching Submersible Weir.